Momentum strategy among countries and industries: evidence from global stock indices and ETFs - Sagoenie, Yashini Gitanjali (2019)
This paper examines several momentum strategies for European countries and industries, namely on individual stock level, national or macromomentum level and for ETFs. This study finds most evidence for momentum presence among individual stocks. Momentum among indices was present, depending on the holding period and the category of industries or countries. Evidence on ETF level was not found. Equally weighted and value weighted methods were used, with the latter being closer to real life but showing less significant results. Comparing the different strategies shows individual stock momentum to consistently outperform macro- and ETFs momentum.